Mental load during cognitive performance in complex regional pain syndrome I. (25th April 2018) - Breimhorst, M.; Dellen, C.; Wittayer, M.; Rebhorn, C.; Drummond, P.D.; Birklein, F.
Abstract: Background: Complex regional pain syndrome (CRPS) is associated with deficits in limb recognition. The purpose of our study was to determine whether mental load during this task affected performance, sympathetic nervous system activity or pain in CRPS patients. Methods: We investigated twenty CRPS‐I patients with pain in the upper extremity and twenty age‐ and sex‐matched healthy controls. Each participant completed a limb recognition task. To experimentally manipulate mental load, the presentation time for each picture varied from 2 s (greatest mental load), 4, 6 to 10 s (least mental load). Before and after each run, pain intensity was assessed. Skin conductance was recorded continuously. Results: Patients with CRPS did not differ from controls in terms of limb recognition and skin conductance reactivity. However, patients with CRPS reported an increase in pain during the task, particularly during high mental load and during the latter stages of the task. Interestingly, state anxiety and depressive symptoms were also associated with increases in pain intensity during high mental load. Conclusions: These findings indicate that high mental load intensifies pain in CRPS. The increase of pain in association with anxiety and depression indicates a detrimental effect of negative affective states in situations of high stress and mental load in CRPS. Significance: The effects of mental load need to be considered when patients with CRPS‐I are investigated for diagnostic or therapeutic reasons.